MAPPING AT A SMALL SCALE. GENERAL REFLECTIONS ON A PARTICULAR EXPERIENCE - Carles Carreras; Sergi Martinez-Rigol; Sergio Moreno (Bollettino della Società Geografica Italiana)
This paper addresses the problem of maps reduction in the work published by geographers in general. Nevertheless this occurs at the time that is available in larger volumes digital information and perform better means of computer assisted Cartography. From the rich experience of publishing many thematic atlas at different scales, both world and urban atlases authors discuss the making of the atlas and complexity in the management of information to improve its representation. It emphasizes the importance of design and the use of color to enhance communication. The conclusion highlights the double value of maps as a result and as a document, and encourages to try to cartographicallyrepresent any type of information, especially the qualitative one.